Mini review of research requirements for radioactive waste management including disposal - Grambow, Bernd (Frontiers in Nuclear Engineering, 2022)
This mini review of research needs in the context of radioactive waste management and disposal has the intention to set the scene for addressing some key research needs in the context of historical developments and of some large industrial mega projects for geological disposal of radioactive waste under development. Well acknowledging that the state of industrial development is quite different in different countries, research in this field of knowledge has a strongly international and long-term oriented character covering both fundamental and applied research including optimization.